2001
DOI: 10.1111/j.1525-1497.2001.10347.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a multimedia tool to improve cardiac auscultation knowledge and skills

Abstract: OBJECTIVE: Today's medical school graduates have significant deficits in physical examination skills. Medical educators have been searching for methods to effectively teach and maintain these skills in students. The objective of this study was to determine if an auscultation curriculum centered on a portable multimedia CD-ROM was effective in producing and maintaining significant gains in cardiac auscultatory skills. DESIGN: Controlled cohort studyPARTICIPANTS: All 168 third-year medical students at 1 medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
3
25
3
Order By: Relevance
“…Current standardized auscultation training for physicians has proven to be an ineffective way to improve most physicians' ability to distinguish abnormal heart, lung, abdominal, and vascular pathologies (4). Previous studies have demonstrated poor auscultation skills in physicians regardless of training level, medical specialty, or country of training (5)(6)(7)(8)(9)(10)(11)(12)(13). A nationwide investigation that tested students' auscultation skills on 12 pre-recorded heart sounds found that the recognition of heart sounds did not improve with lecture-based teaching over 9 months.…”
Section: Introductionmentioning
confidence: 97%
“…Current standardized auscultation training for physicians has proven to be an ineffective way to improve most physicians' ability to distinguish abnormal heart, lung, abdominal, and vascular pathologies (4). Previous studies have demonstrated poor auscultation skills in physicians regardless of training level, medical specialty, or country of training (5)(6)(7)(8)(9)(10)(11)(12)(13). A nationwide investigation that tested students' auscultation skills on 12 pre-recorded heart sounds found that the recognition of heart sounds did not improve with lecture-based teaching over 9 months.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, only a few innovative approaches have been used to teach auscultation. The only change since the introduction of auscultation of mannequins in the 1970s has been in the presentation of the findings, which were formerly presented using audio cassettes and vinyl records instead of digital technology (22).…”
mentioning
confidence: 99%
“…In addition to clerkship rotations, current teaching methods range from classroom lectures and courses, 10 and discussion and audiotape, 4 to heart sound simulators 11 and computer-assisted instructions. 12 None of these methods have been widely adopted or shown to be clearly superior.…”
Section: Introductionmentioning
confidence: 99%